Does Evaluation Improve Performance? – A Case Study of Japanese Public Libraries – - Shimoyama, Kanako; Nishiura, Minako; Naka, Hajime; Tsuji, Keita; Itsumura, Hiroshi (Qualitative and Quantitative Methods in Libraries, 2017)
This study explores the effectiveness evaluation program in public libraries by conducting empirical analysis of selected Japanese public libraries.